2021
DOI: 10.46827/ejmms.v6i4.1144
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relationship Marketing on Customer Loyalty in the Tour and Travel Companies in Malaysia During Cov-19 Pandemic: Parallel Mediation of Social Media and Relationship Quality

Abstract: The aim of this research was to examine the parallel mediating effect of social media and relationship quality between relationship marketing and customer loyalty. A series of regression analysis provided the statistical result that tested the hypothesis proposed in this research. The total population of the travel and tourism firms registered with the Ministry of Tourism, Arts and Culture was 4746. The results of this study were obtained from data collected through 361 out of 600 self-administered questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…As technology has developed, social media has emerged as one of the most efficient eco-friendly channels for green marketing (Kanapathipillai, 2021). Marketers can leverage the social media platform's controllable elements to sway their target market's opinions, information, and behaviour (Kanapathipillai & Mahbob, 2021). Interesting conclusions include environmental concerns and consumer beliefs that influence their environmental views, eco-labelling (EL), green packaging and branding (GPB), green products, premium pricing (GPPP), and eco-products (EP).…”
Section: Discussionmentioning
confidence: 99%
“…As technology has developed, social media has emerged as one of the most efficient eco-friendly channels for green marketing (Kanapathipillai, 2021). Marketers can leverage the social media platform's controllable elements to sway their target market's opinions, information, and behaviour (Kanapathipillai & Mahbob, 2021). Interesting conclusions include environmental concerns and consumer beliefs that influence their environmental views, eco-labelling (EL), green packaging and branding (GPB), green products, premium pricing (GPPP), and eco-products (EP).…”
Section: Discussionmentioning
confidence: 99%
“…The survey concluded that mobile payments and transactions were crucial for Malaysian consumers via mobile technologies (Kanapathipillai & Kumaran, 2022;Benedict, 2020). They also indicated that customer loyalty could be promoted through quality mobile technologies (Kanapathipillai & Mahbob, 2021).…”
Section: Mobile Technology Acceptancementioning
confidence: 99%
“…Using the theoretical approach that will be taken in this part, we will be able to gain a broader understanding of how customers' use of social media promotes the qualities of relationship marketing that ultimately lead to customer loyalty. Additionally, previous research has shown that social network marketing is an essential component in modifying customer loyalty, which is one of the outcomes of relational marketing, as well as customer purchase intention (Kanapathipillai & Mahbob, 2021). With the advent of the Internet, consumers can be more aware of products and services as well as be in contact with vendors on a more frequent basis, thus increasing brand loyalty (Hutter K. et al, 2018).…”
Section: Relationship Between Social Media and Customer Loyaltymentioning
confidence: 99%
“…Researchers have examined the impact of the relationship between Service Quality and Consumer Loyalty, as well as the moderating effect of social media on the relationship between them. Studies have shown that social media and the quality of service affect customer loyalty in the long run (Kanapathipillai & Mahbob, 2021). A company's overall performance can be assessed by comparing its performance to the customer's general expectations of how that particular industry's businesses should perform and how those expectations compare with the experience of a particular service firm (Parasuraman et al, 1988).…”
Section: Social Media As a Moderator 341 Moderating Effect On The Cor...mentioning
confidence: 99%